The Application of GeographicalInformation System (GIS) in Project Management to MonitorConstruction Site Progress and Scheduling - Nazmi, Nur Hidayah (Universiti Teknologi PETRONAS, 2018)
Construction industry has huge amount of data that requires proper handling and new alternative such as Geographical Information System (GIS) to improve project planning and progress monitoring. Until recently project progress monitoring was done and represented by scheduling and shown as bar chart that cannot be easily visualized. Therefore, the objective of this study is to examine the potential of integrating project management and GIS to monitor construction progress. The advantage of utilizing GIS in construction progress monitoring was also discussed. A virtual house construction is chosen as a project monitored while AutoCAD, ArcGIS and construction schedule used as tools in this study. Using GIS, progress monitoring was presented in 3D, which gives more visualization of the actual progress on-site. Construction progress monitoring in 3D not only gives more instinctive perspective of the construction sequence yet enables all parties to see the construction progress amid any phase of the construction stage.